Pengaruh Fasilitas Belajar, Minat Belajar, Lingkungan Belajar dan Motivasi Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS SMK Kabupaten Tanah Datar: Kajian - Hayatul Azma (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This research is aimed to see: (1) The influence of learning facilities toward students learning motivation in social science subject of vocational schools in Tanah Datar Regency (2) The influence of learning interest toward students learning motivation in social science subject of vocational schools in Tanah Datar Regency (3) The influence of learning environment toward students learning motivation in social science subject of vocational schools in Tanah Datar Regency (4) The influence of learning facilities toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency (5) The influence of learning interest toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency (6) The influence of learning environment toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency (7) The influence of learning motivation toward students learning achievement  in social science subject of vocational schools in Tanah Datar Regency. The kind of this research is causal descriptive. The research population is all students at grade XI of vocational schools in Tanah Datar Regency. Number of the population is 750 students in 2016/2017 academic year. The sample was taken by using the technic of Proportional Random Sampling. The research sampling is 261 students out of the whole population. Primary data in this research is taken from questionnaire given to the respondents, and the secondary data, is related to the research object which is presented by other authorities in the form of students learning achievement in final semester examination (UAS) in social science subject. The technic of data analysis is path  analysis with SPSS program 15.0 Version. The research findings are: (1) Learning facilities has significant influence  toward students learning motivation in social science subject of vocational schools in Tanah Datar Regency (2) Learning interest has significant influence  toward students learning motivation in social science subject of vocational schools in Tanah Datar Regency (3) Learning environment has significant influence  toward students learning motivation in social science subject of vocational schools in Tanah Datar Regency (4) Learning facilities have significant influence  toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency(5) Learning interest has significant influence  toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency(6) Learning environment has significant influence  toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency(7) Learning motivation has significant influence  toward students learning achievement in social science subject of vocational schools in Tanah Datar Regency.